The Social Media Content Production Process for Radio Global FM Surabaya’s Instagram Account - Kadishya Aditri Kurnia; Yuli Candrasari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The digital transformation of the radio broadcasting industry requires a paradigm shift from traditional audio-centric models to integrated multi-platform strategies. This study examines the content production process of the @globalfmsby Instagram account to understand how Radio Global FM Surabaya maintains its relevance among modern women and families. Employing a descriptive-operational case study approach with immersive participatory observation, this research identifies three critical production phases: pre-production, production, and post-production. Findings reveal that the station utilizes a structured methodology involving audience-based content pillars, visual assets synchronized with brand identity, and the application of AIDA copywriting techniques bolstered by analytical evaluation. The results demonstrate that effective media convergence is not the byproduct of spontaneous creativity but the result of rigorous, data-driven planning and systematic content management. This study contributes to the literature by providing a professional framework for radio stations seeking to harmonize their broadcast heritage with the requirements of the social media attention economy, ensuring sustainable audience engagement in an increasingly fragmented digital environment.